Professional Ethics and Disciplinary System in the KCA - Ukimeraj, Albulena (European Journal of Economics and Business Studies, 2016)
The term “ethics” comes from the Greek word ’ethos/ethikos’, which means ’tradition, custom or habit". On the other hand, the science that addresses the requirements/duty to act ethically is called Deontology. In exercising the legal profession, Deontology is found as a discipline incorporating a set of principles and rules which must be acknowledged and adhered to by an exercising lawyer in his/her profession. The conduct of lawyers must be exemplary both in exercising profession and outside, in accordance with the dignity inherent to the profession. In recognizing principles and rules of the Code of Professional Conduct and deontology, lawyers must also adhere in their own professional conduct. In exercising their functions, all lawyers are under oath and must live to the commitment of strict adherence and full willingness to an Ethical Code of the profession. The Code of ethics determines the rules of behaviour, which must be adhered to by all lawyers in exercising their profession and rendering their services, to maintain and uphold the dignity and reputation of the Bar Profession. Failure to know the code of ethics does not justify any breach that a lawyer may commit. The idea of addressing this topic stems from the fact that often, lawyers as legal professionals come to confront with their Code of Professional Ethics. Therefore, considering the role and relevance of ethics in the bar profession, in this paper, I have elaborated on the legal grounds of KCA foundation, the regional coverage of the KCA, with a special emphasis on the professional legal ethics and the disciplinary system established by the Chamber of Advocates of Kosovo, a constitutionally established institution, disciplinary proceedings and measures imposed on the lawyers in case of breaches of their own Professional Ethics, concluding with basic principles of conduct and service provision by lawyers.